PENGARUH FASILITAS DAN LOKASI TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING (STUDI KASUS KONSUMEN AWI FUTSAL LAOK JANG-JANG, SUMENEP) - Ach. Noval Annas; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT his study aims to determine and analyze the influence of facilities and locations on customer loyalty through satisfaction as an intervening variable. In Sumenep there are several futsal courts, one of which is Awi Futsal Loak Jang-Jang which was established since 2015 until now the study population was 4200 population for 3 months and the sample used in this study was 98 respondents of Awi Futsal Laok Jang-Jang, Arjasa, Sumenep customers. Data collection is done by distributing questionnaires. Analysis of the data used in this study using validity, reliability, normality, path analysis, t test and sobel test. The results showed that facilities have a direct effect on customer satisfaction, facilities have no direct effect on customer loyalty, location has a direct effect on customer satisfaction, location has a direct influence on customer loyalty, and customer satisfaction does not have a direct influence on customer loyalty. Customer satisfaction cannot mediate between facilities and locations with customer loyalty.Keywords: Facility, Location, Customer Satisfaction, Customer Loyalty